Specialized Therapeutic Assessment-Based Recovery-Focused Treatment for Young People With Self-Harm: Pilot Study - English, Oliver; Wellings, Christy; Banerjea, Partha; Ougrin, Dennis (Frontiers in Psychiatry, 2019)
Background: Suicide is the second leading cause of death in young people worldwide. Self-harm is the strongest predictor of death by suicide. There is increasing evidence that psychological therapies are efficacious in treating self-harm in adolescents. However, studies so far have predominantly focused on highly selective groups of adolescents and have investigated interventions that require intensive training and considerable expense. Methods: We conducted a pilot study of a novel psychological therapy package, Specialized Therapeutic Assessment-Based Recovery-Focused Treatment (START) that consists of Therapeutic Assessment followed by treatment in one of three modules, depending on adolescents’ needs and preferences: Solution Focused Brief Therapy, Cognitive Behavior Therapy (CBT), or Mentalization Based Treatment. Adolescents (12–17) with at least one self-harm episode in the previous 6 months referred for community treatment, who had no intellectual disability, psychosis or autism were eligible for START. The primary outcome measure was the number of self-harm (regardless of suicidal intent) episodes 6 months before and 6 months after commencing START. Secondary outcomes included measures of psychopathology, functional impairment and family satisfaction. Results: Twenty-one consecutively referred adolescents were recruited and 15 received a therapeutic module of START: three received Solution Focused Brief Therapy, nine CBT, and three Mentalization Based Treatment. There was a statistically significant reduction in the number of self-harm episodes from a mean of 7.93 (SD = 12.26) to 1.00 (SD = 1.47), p < 0.02 following START. There was also a significant reduction in self-harm episodes, Revised Children’s Anxiety and Depression Scale scores and a statistically significant improvement in Children Global Assessment Scale scores for the CBT group alone. There were no significant differences in any other outcomes. Most families were somewhat or very much satisfied with the intervention. Conclusion: The results show that START was associated with a reduction in self-harm and depression and anxiety symptoms, which could indicate that START should be rigorously studied in a randomized control trial (RCT). However, the model had difficulties in its implementation, with CBT being only module that was offered to enough young people to allow before and after analysis. CBT appears to be the most promising module in treating adolescents with self-harm referred to community mental health services.